Benefit of some associations as intracanal medication - Zumárraga Paredes, Maria José (2017)
When it is necessary to complete a treatment in more than one appointment, it is recommended to place an intracanal medication in order toavoidthedevelopmentofmicroorganisms. Thereareseveraloptions; however, it dependsontheprofessionaltodecidewhichmedication is suitableforeachcase, hencethe idea of an associationbetweenthe different intracanalmedications. Inview of the antimicrobial, reducing, and anti-inflammatory properties of calcium hydroxide, an association with chlorhexidine, anti-inflammatory, antibiotics or others substances has been sought. Once a paste of calcium hydroxide and chlorhexidine with different concentrations is prepared, the renewal of the tissue and microbial elimination was observed; however, this action did not outweigh the action of the chlorhexidine isolated, then we conclude that there is no potentiation in the combination of these drugs. On the other hand, some studies show that the chlorophenol camphorated has showed increasing the action of the calcium